Correlation analysis between renal anatomical factors and residual stones after an ultrasound-guided PCNL - Zhu, Shusheng; Fan, Yanpeng; Hu, Xia; Shao, Mingming (Frontiers in Surgery, 2023)
Introduction: To predict the factors of residual stones after percutaneous nephrolithotomy (PCNL) by analyzing the characteristics of renal anatomical structure in intravenous urography (IVU), so as to make a reasonable operation plan, reduce the risk of residual stones in PCNL and improve the stone free rate (SFR). Methods: Retrospective study was performed between January 2019 and September 2020 for patients treated by PCNL. According to the results of kidney ureter bladder（KUB）review after PCNL, 245 patients were divided into residual stones group (71 cases, stone size＞4mm) and stone free group (174 cases, stone size ≤ 4mm). Independent sample t-test was used to analyze the age, the length and width of channel calices, the angle between channel calices and involved calices, the length and width of involved calices; The gender, the channel types, the number of channels, the degree of hydronephrosis and the number of involved calices were analyzed by chi square test. P＜0.05 was considered statistically significant. At the same time, Logistic regression analysis was carried out to explore the independent influencing factors of stone free after PCNL. Results: A total of 71 cases developed residual stones after surgery. The overall residual rate was 29.0%. The width of channel calices (p=0.003), the angle between channel calices and involved calices (p=0.007), the width of involved calices (p＜0.001), the channel types (p=0.008), and the number of involved calices (p＜0.001) were significantly correlated with residual stones after PCNL. Logistic regression analysis showed that the width of channel calices (p=0.003)，the angle between channel calices and involved calices (p=0.012)， the width of involved calices (p＜0.001)，the channel types (p=0.008) and the number of involved calyces (p＜0.001) were the independent influencing factors of stone free after PCNL. Conclusion: Larger caliceal neck width and angle can reduce the risk of residual stones. The more calyces involved, the higher risk of residual stones. There was no difference between F16 and F18, but F16 had higher SFR than F24.